Reaqui: um aplicativo para o estudo das reações químicas do cotidiano - Cortez Filho, Ajanildo Soares (Brasil, 2021)
The arrival of Information and Communication Technologies (ICTs) has caused great impacts due to the rapid technological evolution, contributing to the implementation of teaching strategies through a variety of resources that favor the improvement of the teaching-learning process. It is observed that the development of applications has been helping teachers in classrooms, making them more didactic and arousing student interest in the subject. In this sense, the work aimed to develop an application for the study of daily chemical reactions in order to make the teaching and learning process dynamic and attractive. The methodology consisted, firstly, in a bibliographical survey to compose the theoretical foundation and define an initial proposal. From this, the application development was carried out, based on the Cascade Life Cycle, which includes the perception of the REAQUI application, the software documentation, as well as its implementation. Finally, the usability of the application was evaluated with the teachers, in order to validate its use and the features developed.